Comparative analysis of the advantages and disadvantages of collaborative robot control methods within Industry 5.0 - Yevsieiev, V.; Gurin, D. (LLC SPC «InterConf», 2023)
Industry 5.0 represents an evolution of industry in which robotics and automation focus on close collaboration between humans and robots . This means that collaborative robots play a key role in Industry 5.0, and management methods must support their collaboration with humans. Analyzing publications, at this point in time there are the following methods for managing collaborative robots within Industry 5.0.
Keywords: Industry 5.0; collaborative robot